PENGEMBANGAN PERANGKAT PEMBELAJARAN KONTEKSTUAL PADA MATERI PECAHAN - Astuti, Robia (JURNAL E-DUMATH, 2016)
The purpose of this study is to develop the set of contextual teaching learningmodel which increase the quality of math learning. The population of this researchare the students on VII class of SMPIT-Al-Munir Sukoharjo III in the academicyear 2014-2015 that consist of 28 students. In this research, all of the member ofpopulation be the sample because the population is less than 30. In developing theset of learning, the researcher uses 4-D model (Define, Design, Develop, andDisseminate). The data collecting technique used was test, questionnaire, andobservation (observation the application of lesson plan and observe the studentsâactivity). The research finding namely set of learning by using contextual learningmodel that consist of lesson plan, studentsâ worksheet and the test of the learningachievement that is measured from the ability in activate the students and teacherwhose all of them included in good category.Keywords: contextual teaching learning model, 4-D model